Optimization of novel monobactams with activity against carbapenem-resistant Enterobacteriaceae – Identification of LYS228. Issue 4 (15th February 2018) - Reck, Folkert; Bermingham, Alun; Blais, Johanne; Capka, Vladimir; Cariaga, Taryn; Casarez, Anthony; Colvin, Richard; Dean, Charles R.; Fekete, Alex; Gong, Wanben; Growcott, Ellie; Guo, Hongqiu; et al.
Graphical abstract: Abstract: Metallo-β-lactamases (MBLs), such as New Delhi metallo-β-lactamase (NDM-1) have spread world-wide and present a serious threat. Expression of MBLs confers resistance in Gram-negative bacteria to all classes of β-lactam antibiotics, with the exception of monobactams, which are intrinsically stable to MBLs. However, existing first generation monobactam drugs like aztreonam have limited clinical utility against MBL-expressing strains because they are impacted by serine β-lactamases (SBLs), which are often co-expressed in clinical isolates. Here, we optimized novel monobactams for stability against SBLs, which led to the identification of LYS228 (compound 31 ). LYS228 is potent in the presence of all classes of β-lactamases and shows potent activity against carbapenem-resistant isolates of Enterobacteriaceae (CRE).